Outcome of Very Late Relapse in Patients with Hodgkin's Lymphomas - Francesco Gaudio; Annamaria Giordano; Vincenzo Pavone; Tommasina Perrone; Paola Curci; Domenico Pastore; Mario Delia; Clara de' Risi; Alessandro Spina; Vincenzo Liso; Giorgina Specchia (Advances in Hematology)
Recurrences of Hodgkin's Lymphoma (HL) 5 years after the initial therapy are rare. The aim of this study is to report a single centre experience of the clinical characteristics, outcome, and toxicity of pts who experienced very late relapses, defined as relapses that occurred 5 or more years after the achievement of first complete remission. Of 532 consecutive pts with classical HL treated at our Institute from 1985 to 1999, 452 pts (85%) achieved a complete remission. Relapse occurred in 151 pts: 135 (29.8%) within 5 years and 16 over 5 years (3.5%, very late relapses). Very late relapses occurred after a median disease-free interval of 7 years (range: 5–18). Salvage treatment induced complete remission in 14 pts (87.5%). At a median of 4 years after therapy for very late relapse, 10 pts (63%) are still alive and free of disease and 6 (37%) died (1 from progressive HL, 1 from cardiac disease, 1 from thromboembolic disease, 1 from HCV reactivation, and 2 from bacterial infection). The probability of failure-free survival at 5 years was 75%. The majority of deaths are due to treatment-related complications. Therapy regimens for very late relapse HL are warranted to minimize complications.